2017
DOI: 10.3892/etm.2017.5121
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of 146b‑5p promotes inflammation in atherosclerosis‑associated foam cell formation by targeting TRAF6

Abstract: Abstract. Atherosclerosis (AS) is a chronic inflammation in response to lipid accumulation. Increasing evidence has demonstrated that numerous microRNAs (miRs) have critical roles in inflammatory responses. A previous study suggested that miR-146b-5p is possibly associated with AS; however, its exact role has remained largely elusive. The present study aimed to investigate the potential role of miR-146b-5p in AS and to explore the underlying mechanism. Fist, the levels of miR-146b-5p were determined in foam ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…In this study, we identified TRAF6 as the target of miR146b‐5p in mediating the effects of miR146b‐5p on tumor growth. Our results are consistent with previous reports showing that miR146‐5p targets TRAF6 to regulate relevant cellular functions . It is interesting that miR146‐5p is able to both suppress and promote tumor growth by targeting the same molecular.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we identified TRAF6 as the target of miR146b‐5p in mediating the effects of miR146b‐5p on tumor growth. Our results are consistent with previous reports showing that miR146‐5p targets TRAF6 to regulate relevant cellular functions . It is interesting that miR146‐5p is able to both suppress and promote tumor growth by targeting the same molecular.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous reports showing that miR146-5p targets TRAF6 to regulate relevant cellular functions. 11,13,16 It is interesting that miR146-5p is able to both suppress and promote tumor growth by targeting the same molecular. In fact, in our study, we also found that TRAF6 knock out mice showed suppressed orthotopic tumor growth to the same extent as treatment of miR146-5p inhibitor in wild type mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, miRNA-30e-3p and miRNA-455-3p accelerate vascular inflammation and remodelling by increasing MAPK/NF-κB pathway in rats [ 79 ]. Additionally, up-regulation of miRNA-146b-5p and miRNA-19b increase vascular inflammation and AS via NF-κB activation, foam cell formation, ECM protein synthesis and deposition and plaque formation [ 80 ]. Additionally, downregulation of miRNA-30c-5p promoted macrophage foam cell formation and increased IMT while increased miRNA-30c-5p expression prevented such thickening in human [ 81 ].…”
Section: Abnormalities In Dna and Histone In Asmentioning
confidence: 99%